A Study on victims of school violence in Korea - KIM, Min Ji (KDI School, 2017)
South Korea is on the verge of transforming into a multicultural society. As recently as 50 years ago, diverse group of immigrants stormed into the country looking for new opportunities available in the newly emerging economy. Now there are over 2 million foreigners that reside in South Korea forming families brining different cultures together in households. Referred to as multicultural families, this particular family type brings forth different challenges to the Korean society that need to be acknowledged and dealt with Responding to the social needs, this paper will focus specifically on students from the multicultural families and challenges they face in school scenes. It will acknowledge the problem of violence that students with multicultural background encounter at schools, define the factors behind victimization and suggest necessary measures that need to be taken to respond to the problem.
Thesis(Master) --KDI School:Master of Public Policy,2017